The Influence Of Learning Mathematics Software Geogebra On The Ability Of Creative Thinking Of Students - Mebratu Mulatu Bachore (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to determine the ability of creative thinking of students that the process of learning using learning mathematics software geogebra is higher than using conventional learning models. This research is a quantitative type of Quasy Experimental Design. The subjects of this study were students with a population of 184 students. Sample in this research is class as the experimental class using learning mathematics software geogebra, class as the control class using conventional learning models. Data analysis techniques using test normality test Shapiro-Wilk test and homogeneity test with Levene. Proceed with the hypothesis test using t–Test independent sample t-test. Based on the results of the analysis and discussion of the research data obtained the results that the ability of creative thinking of students that the process of learning using learning mathematics software geogebra is higher than models using conventional learning. Students with the treatment of learning mathematics software geogebra, have the ability to think creatively is better compared to students with the treatment of learning using conventional learning models